Plays well with others : a novel - Brickman, Sophie (William Morrow, an imprint of HarperCollinsPublisheres, 2024)
"It takes a village...just not this one. Annie Lewin is at the end of her rope. She's a mother of three young children, her workaholic husband is never around, and the vicious competition for spots in New York City's kindergartens is heating up. A New York Times journalist-turned-parenting-advice-columnist for an internet start-up, Annie can't help but judge the insanity of it all--even as she finds herself going to impossible lengths to secure the best spot for her own son. As Annie comes to terms with the infinitesimal odds of success, her intensifying rivalry with hotshot lawyer Belinda Brenner--a deliciously hateful nemesis, what with her perfectly curated bento box lunches and effortless Instagram chic--pushes her to the brink. Of course, this newly raw and unhinged version of Annie is great for the advice column: the more she spins out, the more clicks and comments she gets. But when she commits a ghastly social faux pas that goes viral, she's forced to confront the question: is she really any better than the cutthroat parents she always judged?"--